Telaah Ekonomi Politik Peran Investor Dalam Pembangunan Transportasi Publik Di Daerah Wisata Kuta Bali - Emma Ratna Sari Moedy (Universitas Mahendradatta Denpasar, 2020)
Traffic jam is sosial problem in Kuta, Bali, Indonesia. The congestion problem has taken root in tourism destination . The causes are complex. The role of investors in governance in Kuta, Bali, Indonesia, was appointed in the form of writing about public discourse primarily about the implementation of public policy. This discussion and social research was made for business people in Kuta. Comprehensive handling is needed so it is not only handled from one side only. The synergy of the government, private sector and investors is urgently needed in order to be able to provide guarantees for smoothness, certainty, comfort, affordability and better safety. This can only be achieved if the concept of planning is correct, actors are united, government policies support, high public obser- vance and strict enforcement of law enforcement. Continuity and integration between transportation modes is also a prerequisite for better quality levels. Thus, effectiveness and efficiency will be achieved which in turn will support efforts to overcome congestion and ultimately improve the welfare of the community. The face of traffic and public trans- portation is a reflection of Bali’s face as a world tourist destination.